Tacrolimus‐induced thrombotic microangiopathy in orthotopic liver transplant patients: case series of four patients. Issue 3 (27th February 2013) - Nwaba, A.; MacQuillan, G.; Adams, L. A.; Garas, G.; Delriviere, L.; Augustson, B.; DeBoer, B.; Moody, H.; Jeffrey, G. P.
Abstract Thrombotic microangiopathy (TMA) is a potentially fatal complication in solid organ and bone marrow transplant patients, with reported incidence of 0.5–3% and mortality of about 75%. To emphasise the importance of early diagnosis and prompt commencement of therapy results in improved clinical outcomes. A retrospective study of all patients who underwent orthotopic liver transplantation (OLTX) at the Western Australian Liver Transplantation Service from May 1994 to December 2010 was conducted to identify patients who developed tacrolimus‐induced TMA. We identified four patients with tacrolimus‐induced TMA post‐OLTX, derived from a cohort of 104 patients treated with tacrolimus in our institution. The mean age at diagnosis was 40 years, and the mean time of onset was 63 ± 7.5 weeks after OLTX. The indications for OLTX in the four patients were fulminant hepatic failure in three (Wilson disease, paracetamol overdose and post‐partum thrombotic thrombocytopenic purpura) and hepatitis C virus‐related cirrhosis. All patients had tacrolimus post‐OLTX. At diagnosis, tacrolimus was discontinued in all patients, and three of the four patients underwent plasma exchange and all patients improved clinically. Mean duration of follow up was 15 ± 7.5 months. There was no mortality 6 months post‐TMA. Early diagnosis with immediate discontinuation or conversion of calcineurin inhibitors and plasma exchange should be offered to OLTX patients with TMA as it results in good outcomes.